Constructing the Formative Test for Diagnosing Misconceptions of First-Semester High School Biology - Ikhsanudin, Ikhsanudin; Subali, Bambang (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
A misconception is one of the learning obstacles that often occurs in biology class. This study aims to construct a diagnostic instrument to detect misconceptions of biological concepts during the first semester of senior high school and test the quality of the developed instrument. The instrument development model used was a modification of the Oriondo, Dallo-Antonio, and Azwar models. The construction begins with planning the measuring domain and preparing the blueprint for the test instrument. The processes were followed by an instrument seminar, peer review, expert judgment validation, and trying out the test on 885 students. In addition, an unstructured interview with the teachers determines the feasibility of the test instrument. The test content validity according to the Aiken formula is 0.85; the items have different levels of difficulty and good discriminating power; the number of 62 items fits the partial credit model. The reliability of the test is shown by a Kappa coefficient of 0.47. Thus, the test instrument proved to be valid and reliable. Thirteen teachers from eleven schools stated that the test is worthy of use in learning. For the school level, the instrument meets the criteria of a good test instrument.